Pharmacokinetic parameters and tissue distribution of magnetic Fe3O4 nanoparticles in mice - Jun Wang (Dove Medical Press, 2010)
Jun Wang1, Yue Chen1, Baoan Chen1, Jiahua Ding1, Guohua Xia1, Chong Gao1, Jian Cheng1, Nan Jin1, Ying Zhou1, Xiaomao Li1, Meng Tang2, Xue Mei Wang21Department of Hematology, Zhongda Hospital, Clinical Medical School, Southeast University, Nanjing, People’s Republic of China; 1Department of Physics, University of Saarland, D-266041 Saarbruechen, Germany; 2National Key Laboratory of Bioelectronics (Chien-Shiung Wu Laboratory), Southeast University, Nanjing, People’s Republic of ChinaBackground: This study explored the pharmacokinetic parameters and tissue distribution of magnetic iron oxide nanoparticles (Fe3O4 MNPs) in imprinting control region (ICR) mice.Methods: The Fe3O4 MNPs were synthesized by chemical coprecipitation, and their morphology and appearance were observed by transmission electron microscopy. ICR mice were divided into a control group and a Fe3O4 MNP-treated group. Probable target organs in ICR mice were observed, and the pharmacokinetic parameters and biodistribution of Fe3O4 MNPs in tissues were identified using atomic absorption spectrophotometry.Results: Fe3O4 MNPs were spherical with a well distributed particle diameter, and were distributed widely in various target organs and tissues including the heart, liver, spleen, lungs, kidneys, brain, stomach, small intestine, and bone marrow. The majority of Fe3O4 MNPs were distributed to the liver and the spleen. Fe3O4 MNP levels in brain tissue were higher in the Fe3O4 MNP-treated group than in the control group, indicating that Fe3O4 MNPs can penetrate the blood–brain barrier.Conclusion: These results suggest that the distribution of Fe3O4 MNPs was mostly in the liver and spleen, so the curative effect of these compounds could be more pronounced for liver tumors. Furthermore, Fe3O4 MNPs might be used as drug carriers to overcome physiologic barriers.Keywords: magnetic nanoparticles, Fe3O4, tissue distribution, mice